Engineering sciences:: pharmacokinetics and pharmacodynamics as an inter- and multidisciplinary field - Pires, Jorge Guerra; Maggio, Roberto; Manes, Constanzo; Palumbo, Pasquale (Revista Gestão & Saúde, 2015)
Amongst the entire potential spectrum of expansion of the engineering sciences as an omnipresent field, we might point out the studies of drugs, applied pharmacology, as a good candidate for receiving attention. The common problematic encountered in the literature faced by the industry of drugs is the high cost for drug development and systematic approaches are demanded. On the hope to bring the discussions to engineering’s territory, we borrow several insights from mathematical modeling; it is presented a simple case study, tumor treatment using optimal control, we shall see that it is possible with simple tools already standard in engineering to design an optimal regimen for the tumor therapy, given that the tumor respects our model. On the example presented, we shall see that tools already part of (industrial) production engineering, with exception of optimal control theory, is enough for getting insights. The ideas discussed herein could diminish the cost of drug development if properly extended. As any endeavor, we have challenges, such as to gain the credibility necessary for really using those models in the academy and industry.